If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + y)(xy + -1) = 0 Reorder the terms: (x + y)(-1 + xy) = 0 Multiply (x + y) * (-1 + xy) (x(-1 + xy) + y(-1 + xy)) = 0 ((-1 * x + xy * x) + y(-1 + xy)) = 0 ((-1x + x2y) + y(-1 + xy)) = 0 (-1x + x2y + (-1 * y + xy * y)) = 0 Reorder the terms: (-1x + x2y + (xy2 + -1y)) = 0 (-1x + x2y + (xy2 + -1y)) = 0 Reorder the terms: (-1x + xy2 + x2y + -1y) = 0 (-1x + xy2 + x2y + -1y) = 0 Solving -1x + xy2 + x2y + -1y = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 374=m/23 | | 2/3m-4=12 | | x^2+y^2-4X-6Y+17=0 | | -3/5-2/ | | 13y-7y+y+4y-8y=12 | | 6y+2=4y+12 | | 4(-4+2b)-8(6b-7)=80 | | -1/2*0-2 | | -6(1+n)+4(3n+4)=58 | | (x)=7x^2+2x | | -2(3x+6)=20-4x | | 11p-p-8p-p=19 | | -5(4b-6)-2(5b-2)=4 | | 9h+3=5h | | 30x/(x^3) | | 15z-14z=20 | | -4+20-6-(-18)+(-11)= | | -84+10x=3x+63 | | 3/4--16 | | -5x-15=50 | | -2c+30=24 | | -4+20-6(-18)+(-11)= | | 14z-13z=5 | | -10m+2=-8m-8 | | 13d-12d=1 | | -6x+y = -3 | | x/7-1=-6 | | 230/30=345/x | | M/5=175.3 | | -5/6x-1/9x=-102 | | 6y+5y+4= | | 2/3(-2)-4 |